Wastewater analysis for substance abuse monitoring and policy development - Prichard, Jeremy (Boca Raton : CRC Press, Taylor & Francis Group, 2021)
"This book will explain wastewater analysis (WWA) in the context of substance abuse; discuss the potential implications of WWA as a new method for understanding substance use in a variety of settings; and ignite a discourse with policy makers, criminologists, epidemiologists and other disciplines about the need for collaboration with WWA scientists"--
Preface. Acknowledgements. About the Authors. Chapter 1 Measuring Strategies to Counter the Harms of Substance Use: A Global Overview. Chapter 2 Understanding Wastewater Analysis: How It Works; Its Strengths and Limitations. Chapter 3 Macro Applications of Wastewater Analysis: International Comparisons. Chapter 4 Meso Applications of Wastewater Analysis: National Research. Chapter 5 Micro Applications of Wastewater Analysis: Prisons, Educational Institutions and Workplaces. Chapter 6 Future Directions. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Substance abuse; Sewage -- Sampling; Water -- Sampling; LAW / Forensic Science; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Analytic